2023
DOI: 10.1177/08944393231156634
|View full text |Cite
|
Sign up to set email alerts
|

Do (Not!) Track Me: Relationship Between Willingness to Participate and Sample Composition in Online Information Behavior Tracking Research

Abstract: This paper offers a critical look at the promises and drawbacks of a popular, novel data collection technique—online tracking—from the point of view of sample composition. Using data from two large-scale studies about political attitudes and information consumption behavior carried out in Germany and Switzerland, we find that the likelihood of participation in a tracking study at several critical dropout points is systematically related to the gender, age, and education of participants, with men, young, and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 40 publications
3
7
0
Order By: Relevance
“…Similarly, the fact that top-5 results attract around 90% of all clicks and more than 97% of search visits do not go beyond page 1 of search outputs, underscores the influence search rankings have on user information consumption. The similarity of this finding to the observations regarding the result ranking made by previous studies over a decade ago [ 6 , 7 , 12 , 19 ], underscores the persistence of the observed phenomenon. It can undoubtedly contribute to the "rich-gets-richer" bias and search concentration, but also stresses the importance of reliability and accuracy of the top results.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Similarly, the fact that top-5 results attract around 90% of all clicks and more than 97% of search visits do not go beyond page 1 of search outputs, underscores the influence search rankings have on user information consumption. The similarity of this finding to the observations regarding the result ranking made by previous studies over a decade ago [ 6 , 7 , 12 , 19 ], underscores the persistence of the observed phenomenon. It can undoubtedly contribute to the "rich-gets-richer" bias and search concentration, but also stresses the importance of reliability and accuracy of the top results.…”
Section: Discussionsupporting
confidence: 87%
“…The demographic distributions in the samples are as follows: self-reported gender: CH—43.8% female, DE—44.8% female; age: CH—mean = 43.8, median = 42, DE—mean = 49.3, median = 51; education: CH—3.6% obligatory education, 54.9%—full secondary education, 41.6%—tertiary education, for DE corresponding numbers are 12.9, 51.3, 35.8%; income: CH—7.2% not reported, 37.7% below 3999CHF, 37.1% between 4000 and 6999 CHF, 17.9% above 7000 CHF; DE—3.1% not reported, 48.4% below 1999 EUR, 44.8% from 2000 to 4999 EUR, 3.8% above 5000 EUR. The resulting samples deviate from the actual composition of the population of the corresponding countries—e.g., in our samples, men and people with higher levels of education are over-represented as compared to the actual population; such skewness in the participants willing to participate in web tracking studies was observed in our case and with another study conducted in Germany using a similar recruitment procedure in 2021 [ 6 ]. As extensively discussed in [ 6 ], this is linked to different concerns different groups of participants had about the tracker.…”
Section: Methodssupporting
confidence: 51%
See 3 more Smart Citations